Influence of adaptive mesh refinement and the hydro solver on shear-induced mass stripping in a minor-merger scenario - Schmidt, Wolfgang; Schulz, Jochen; Iapichino, Luigi; Vazza, Franco; Almgren, Ann S. (Astronomy and computing, 2015)
We compare two different codes for simulations of cosmological structure - formation to investigate the sensitivity of hydrodynamical instabilities - to numerics, in particular, the hydro solver and the application of - adaptive mesh refinement (AMR). As a simple test problem, we consider an - initially spherical gas cloud in a wind, which is an idealized model for - the merger of a subcluster or galaxy with a big cluster. Based on an - entropy criterion, we calculate the mass stripping from the subcluster - as a function of time. Moreover, the turbulent velocity field is - analyzed with a multi-scale filtering technique. We find remarkable - differences between the commonly used PPM solver with directional - splitting in the ENZO code and an unsplit variant of PPM in the NYX - code, which demonstrates that different codes can converge to - systematically different solutions even when using uniform grids. For - the test case of an unbound cloud, AMR simulations reproduce - uniform-grid results for the mass stripping quite well, although the - flow realizations can differ substantially. If the cloud is bound by a - static gravitational potential, however, we find strong sensitivity to - spurious fluctuations which are induced at the cutoff radius of the - potential and amplified by the bow shock. This gives rise to substantial - deviations between uniform-grid and AMR runs performed with ENZO, while - the mass stripping in NYX simulations of the subcluster is nearly - independent of numerical resolution and AMR. Although many factors - related to numerics are involved, our study indicates that unsplit - solvers with advanced flux limiters help to reduce grid effects and to - keep numerical noise under control, which is important for - hydrodynamical instabilities and turbulent flows.